0282 Correlation Between Sleep Depth in the Right and Left Cerebral Hemispheres Following Sleep Deprivation, Restriction or Noise Exposure. (27th May 2020) - Younes, M; Kuna, S T; Pack, A I; Schweitzer, P K; Walsh, J K; Smith, M G; Basner, M; Aeschbach, D
Abstract: Introduction: The Odds-Ratio-Product (ORP) is a highly-validated continuous index of sleep depth (range 0=deep sleep; 2.5=full wakefulness). ORP values fluctuate within this range as sleep state changes between wake and different sleep stages. In healthy non-sleep deprived adults, intra-class correlation coefficient of concurrent right vs. left ORP values (R / L coefficient) is typically >0.80. In a recent study R / L coefficient was markedly reduced in many critically-ill patients and these patients failed to be weaned from mechanical ventilation. Given the high prevalence of sleep loss in such patients we hypothesized that reduction in R/L coefficient might result from sleep loss. This retrospective EEG analysis of data from 3 independent research studies investigated if R / L coefficient decreases in pure models of sleep deprivation, restriction or noise exposure during sleep in healthy subjects. Methods: Polysomnograms were obtained from three studies: A) 200 subjects who underwent 36 hours of total sleep deprivation; B) 21 subjects who underwent 4 consecutive nights of sleep restriction (5 hrs. / night); C) 72 subjects who were exposed to intermittent traffic noise events with maximum sound pressure levels ranging from 45–65 dB(A) for 10 consecutive nights. For study A, R / L coefficient was calculated from pre- and post-deprivation sleep studies and the two values were compared. For study B, coefficient was calculated at baseline and in each restriction night. For study C, the coefficient was calculated in each of the 10 exposure nights and the slope of the change was calculated. Results: In study A, the coefficient decreased from 0.82±0.12 at baseline to 0.74±0.16 after sleep deprivation (p &lt 0.0001). In study B, the coefficient decreased from 0.83±0.11 at baseline to 0.75±0.15 on the 4 th restriction night (p &lt 0.01). In study C, coefficient decreased at a rate of 0.003±0.001 per exposure night (p &lt 0.001). Conclusion: The correlation between sleep depth in the right and left hemispheres deteriorates following sleep deprivation, restriction or noise-induced sleep fragmentation. Support: NIH P50 HL060287